Subfoveal Choroidal Thickness in Relation to Axial Length and Refractive Errors in Adults Aged 20-40 (Annals of Medical Research, 2021)
Aim: The aim of this study is to investigate the association between subfoveal choroidal thickness, ocular axial length, and refractive errors in healthy adults.Materials and Methods: A hundred eyes of 50 patients were included in this study. A full ophtalmic examination including best corrected visual acuity, refractive levels, and interferometric ocular axial length was applied to all the patients. The submacular choroidal was imaged using enhanced depth imaging spectral domain optical cohorence tomography. Subfoveal choroidal thickness was measured by two diifferent experts using visual inspection and manual fitting of the choroidal borderlines.Results: Of the 50 subjects, 24 were males and 26 were females. The results of the applied measurements were as follows: mean age: 28,9(±6,8); visual acuity: 0,95±0,16; mean subfoveal choroidal thickness: 302,64μm(±52,07); mean axial lentgh: 23,59mm(±0,94); mean intraoculer pressure 14,5±2,3; and mean spheric equivalent -0,47(±0,97). No significant difference between males and females was observed in terms of mean subfoveal choridal thickness. Multivariable linear regression suggested that age was not associated with subfoveal choroidal thickness (r=-0,247; p=0,106). There was no correlation between axial length and subfoveal choroidal thickness either (r=-0,128; p=0,234). There was, however, a positive correlation between spheric equivalents and subfoveal choroidal thickness (r=0,227; p=0,033).Conclusion: In this study, we found that subfoveal choroidal thickness was significantly associated with spheric equivalent while there was no association between axial length and subfoveal choroidal thickness. We also observed that there was no difference between males and females with regards to subfoveal choroidal thickness.Keywords: Choroidal Thickness; Axial Length.